2018
DOI: 10.1021/acsami.8b01516
|View full text |Cite
|
Sign up to set email alerts
|

On the Stability of NaO2 in Na–O2 Batteries

Abstract: Na-O batteries are regarded as promising candidates for energy storage. They have higher energy efficiency, rate capability, and chemical reversibility than Li-O batteries; in addition, sodium is cheaper and more abundant compared to lithium. However, inconsistent observations and instability of discharge products have inhibited the understanding of the working mechanism of this technology. In this work, we have investigated a number of factors that influence the stability of the discharge products. By means o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…Moreover, when discharged electrode containing NaO 2 is exposed to flowing O 2 for 1 hour, Na 2 O 2 ⋅ 2H 2 O immediately appears as identified by XRD. In comparation, NaO 2 that does not experience flowing O 2 can be stored in a vacuum pouch for 110 days with a very slow decomposition rate, and no Na 2 O 2 ⋅ 2H 2 O is detected . Stainless steel and glass testing setup generate NaO 2 and Na 2 O 2 ⋅ 2H 2 O as the major discharge product, respectively.…”
Section: Challenges At the Cathodesmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, when discharged electrode containing NaO 2 is exposed to flowing O 2 for 1 hour, Na 2 O 2 ⋅ 2H 2 O immediately appears as identified by XRD. In comparation, NaO 2 that does not experience flowing O 2 can be stored in a vacuum pouch for 110 days with a very slow decomposition rate, and no Na 2 O 2 ⋅ 2H 2 O is detected . Stainless steel and glass testing setup generate NaO 2 and Na 2 O 2 ⋅ 2H 2 O as the major discharge product, respectively.…”
Section: Challenges At the Cathodesmentioning
confidence: 95%
“…Recent research indicates that Na 2 O 2 ⋅ 2H 2 O is possibly originated from NaO 2 , which is initially generated in ether‐based Na−O 2 batteries and undergoes decomposition to Na 2 O 2 ⋅ 2H 2 O. As shown in Figure , the key factor that drives the conversion of NaO 2 into Na 2 O 2 ⋅ 2H 2 O is water, which can be introduced from feeding gas, electrolyte, and leakage of the test setup and characterization holder .…”
Section: Challenges At the Cathodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the decomposition of NaO 2 was accompanied by an unknown phase, which can transform into Na 2 O 2 ·2H 2 Oa fter prolonged exposure to solvent or moisture. [38] In another in operando study employing electrochemical STEM, Lutz et al observed the formation and dissolution of the NaO 2 product. They observed that the NaO 2 cubes formed are more complex,c ontaining shells of different composition surrounding the NaO 2 ,a nd that both the reduction and oxidation of the NaO 2 occurs through as olution-mediated process.…”
Section: Stabilitymentioning
confidence: 99%
“…They found that the decomposition rate is over 40 times slower in the absence of Na metal. Additionally, the decomposition of NaO 2 was accompanied by an unknown phase, which can transform into Na 2 O 2 ⋅ 2 H 2 O after prolonged exposure to solvent or moisture …”
Section: Sodium‐oxygen Batteriesmentioning
confidence: 99%